Sensing the structural behavior: A perspective on the usefulness of monitoring information for bridge examination - Bertola, Numa; Reuland, Yves; Brühwiler, Eugen (Frontiers in Built Environment, 2023)
Managing existing civil infrastructure is challenging due to evolving functional requirements, material aging, and climate change. With increasingly limited economic, environmental, and material resources, more sustainable solutions for practical asset management are required. Significant efforts have been recently made to monitor civil infrastructure, such as bridges. In-situ measurements are collected with the aim of making more accurate evaluations of the structural capacity. Monitoring data collected through bridge load testing, continuous condition monitoring, and non-destructive tests may provide structural-behavior information that could significantly influence structural-safety assessments. Nonetheless, these monitoring techniques are often costly, and the monitoring costs may not always justify the benefits of the information gained. This paper proposes a perspective of the potential impact of monitoring activities on infrastructure management. A full-scale bridge in Switzerland is used as an example. Future research needs are also proposed.